Dengue, Chikunguña and Zika in Colombia 2015-2016 (2017)
Objective: To describe the epidemiological trends during 2015 - 2016 of three of the most important arthropod-borne virus infections occurred in the country in recent years: Zika, Dengue and Chikunguña. Materials and Methods: A descriptive study, in which the behavior of these diseases is analyzed from bulletins of the National Institute of Health, during the fifty-two epidemiological weeks of 2016. Results: In 2016, 103.822 cases were reported in the country Dengue (49.9% ♀), 19.566 of Chikunguña (63.3% ♀) and 106.559 of Zika (66.4% ♀). The most affected population was in the range of 25 to 39 years-old, but significant differences in the average age of the three conditions (p<0.05) were observed. Most reports about Zika infection were based on clinical diagnosis. Conclusions:Implementation of mechanisms that allows a better understanding of the etiology and clinical behavior of these diseases by health actors is required.